Records Committee review for rare bird sighting for Bohemian Waxwing at Marble Beach State Park at Spirit Lake in 1998 - Iowa Ornithologists' Union Records Committeeet al (1998)
Records Committee review for a Bohemian Waxwing at Marble Beach State Park at Spirit Lake in Dickinson County, IA on November 21, 1998. Includes a record review document with votes, e-mail correspondence about the sighting, and original sighting record found in Field Reports-Iowa Bird Life submitted by Lee A. Schoenewe. This document is related to https://avian.lib.iastate.edu/documents/6794/view. Epson - sheet feed